2017
DOI: 10.5935/abc.20170088
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Risk Stratification and Statin Eligibility Based on the Brazilian vs. North American Guidelines on Blood Cholesterol Management

Abstract: Background:The best way to select individuals for lipid-lowering treatment in the population is controversial.Objective:In healthy individuals in primary prevention:to assess the relationship between cardiovascular risk categorized according to the V Brazilian Guideline on Dyslipidemia and the risk calculated by the pooled cohort equations (PCE);to compare the proportion of individuals eligible for statins, according to different criteria.Methods:In individuals aged 40-75 years consecutively submitted to routi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 23 publications
0
6
0
3
Order By: Relevance
“… 35 , 36 Furthermore, the use of statins was more common among patients with RH, which may also be related to the elevated CVR and renal dysfunction risk in this group. 37 Although greater in the RH group, the difference between the prevalence of dyslipidemia in the two groups was lower than the difference found between the percentage of statin use. We must consider that the prescription of this medication is not exclusively dependent on serum cholesterol levels, being mainly associated with the assessment of the patient’s CVR and considering the existence of a contraindication to its use.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“… 35 , 36 Furthermore, the use of statins was more common among patients with RH, which may also be related to the elevated CVR and renal dysfunction risk in this group. 37 Although greater in the RH group, the difference between the prevalence of dyslipidemia in the two groups was lower than the difference found between the percentage of statin use. We must consider that the prescription of this medication is not exclusively dependent on serum cholesterol levels, being mainly associated with the assessment of the patient’s CVR and considering the existence of a contraindication to its use.…”
Section: Discussionmentioning
confidence: 66%
“…We must consider that the prescription of this medication is not exclusively dependent on serum cholesterol levels, being mainly associated with the assessment of the patient’s CVR and considering the existence of a contraindication to its use. 37 …”
Section: Discussionmentioning
confidence: 99%
“…síndrome metabólica, níveis elevados de proteína C-reativa ultrassensível, história familiar de doença arterial coronariana prematura) na Atualização da Diretriz Brasileira, bem como uma "valorização" dos fatores agravantes do risco para decisões de tratamento na diretriz O presente estudo atualiza e expande nosso estudo prévio comparando a V Diretriz Brasileira de Dislipidemias e a Diretriz de Colesterol do ACC/AHA de 2013. 6 Setenta e cinco porcento da amostra da presente análise correspondem aos indivíduos incluídos no estudo anterior; os demais referem-se aos indivíduos atendidos no mesmo serviço mais recentemente. Portanto, nossos resultados permitem uma avaliação do impacto das mudanças na versão atualizada da diretriz brasileira sobre a estratificação de risco e elegibilidade ao tratamento com estatina.…”
Section: Discussionunclassified
“…[1][2][3][4][5] Em um estudo prévio, observamos que uma proporção consideravelmente maior da população em prevenção primária foi considerada elegível a receber estatina com base nas recomendações da V Diretriz Brasileira de Dislipidemias, em relação à diretriz do American College of Cardiology (ACC)/American Heart Association (AHA) para o manejo do colesterol de 2013. 6 Este achado ocorreu como consequência de uma clara discrepância entre a estratificação do risco cardiovascular segundo a diretriz brasileira 1 e o risco calculado pelas pooled cohort equations (PCE), conforme recomendado pela diretriz do ACC/AHA. 3,7 A Diretriz Brasileira de Dislipidemias foi atualizada em 2017.…”
Section: Introductionunclassified
“…Cardiovascular risk scores, such as the Framingham score, have been strongly recommended by clinical guidelines on the assessment of cardiovascular risk. 1 However, several studies have shown limitations for their use, 2 , 3 particularly in patients at intermediate risk, young patients with a definite family history, and women. Among different tools aimed at improving risk stratification by complementary methods, the use of genetic information has been proposed to enhance risk prediction.…”
mentioning
confidence: 99%